An Analysis of the Portfolio Structure of Open Pension Funds - Bolisęga, Maciej (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The system of open pension funds (OFE) is a consequence of the pension re-organisation that took place in 1999 in Poland. Since then, thanks to the size of assets under management, OFEs have become one of the most important players on the Polish financial market. The aim of this analysis is to examine aggregated portfolio structure in terms of both debt instruments and shares. The study also comprises a description of legal restrictions regarding investment policy. Two approaches have been implemented for the shares of an aggregated portfolio. One involves an analysis focused on stocks in which OFEs invested the highest absolute amount. The other approach focused on stocks in which OFEs had obtained the highest shareholder stake. Our results suggest that, in terms of relative stake of shareholders, OFEs invest the most in medium-size companies. However, further studies must take into account more factors in order to provide a more comprehensive view of the issue.